The Effect of Pre-reading Strategies on Adult ESL Learners’ Reading Comprehension (المجلة الدولية للعلوم التربوية والآداب, 2024)
Reading comprehension plays a significant role in second language learning. Yet, it is still the most challenging skill to acquire for second language learners. Because reading is an active process, research indicated that readers need to apply different strategies before, during, and after reading. This study aimed to examine the effect of pre-reading strategies on reading comprehension of adult ESL learners. Fourteen adult ESL students participated in the study. Data were collected through pre and post reading comprehension tests during a period of three weeks. Students’ performance was measured before they were introduced to the pre-reading strategies and was compared to their performance after learning and applying those strategies. Results showed that students’ scores increased significantly after using pre-reading strategies.